ANALISIS PENGARUH KESEMPATAN KERJA, TINGKAT PENDIDIKAN DAN TINGKAT KESEHATAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI BALI - Manullang, Tasya Oktavia; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 12 (2024): Vol.13.No.12. DESEMBER 2024 [831-914], 2025)
Bali is regarded as one of the world's top travel destinations. The presence of poverty in an area serves as a reminder of the significance of managing more optimal development performance, which includes lowering the poverty rate in Bali Province. Despite the comparatively low poverty rate, there is still a sizable regional disparity in poverty levels. The purpose of this study is to analyse two aspects of poverty rates in Bali Province: 1) the simultaneous impact of employment opportunities, health, and education levels on rates of poverty in cities and regencies; and 2) the partial impact of these factors on rates of poverty in cities and regencies. The study's findings suggest that the government should concentrate its efforts on lowering the poverty rate in Bali Province's regencies and municipalities, particularly in those with  comparatively higher rates. This can be achieved by improving the quality of job opportunities and guaranteeing more equitable access to health and education services, particularly in areas that are located quite a distance from the city centre. JEL Classification: E2, F6, H5